Social aspect of urban agriculture with examples from Croatia - Ana Poštek; Ivica Kisić; Marija Cerjak; Luka Brezinščak (Journal of Central European Agriculture, 2021)
As the world's population increases every day, so does their need for food. Most of the world's population lives in urban centres away from food production sites. To reduce food dependence, the urban population turns to food production within the city, urban agriculture (UA). Attention to urban agriculture has increased rapidly during the last couple of decades. Enthusiasm for UA is growing on an international and domestic level, also with the scholar community. Still, there are policy makers that struggle to implement UA with city planning. Over time, various forms of agriculture production in the city have evolved, divided into three main categories: urban agriculture, peri-urban agriculture, and urban farms. In addition to its multiple impacts (economic and ecological), UA has a significant holistic approach. It appears differently depending on the context. Some of the social effects of urban agriculture can be: fostering activism, gender equality, social cohesion and social inclusion, education, and preservation of cultural heritage. There are many examples of urban agriculture in the world, often with an economic or environmental role as the primary one. However, in this paper, firstly, we analyse various social aspects, and secondly, we present examples from Croatia, where the primary purposes are social benefits.